2018
DOI: 10.1002/we.2159
|View full text |Cite
|
Sign up to set email alerts
|

Classifying rotor‐layer wind to reduce offshore available power uncertainty

Abstract: Rotor-layer wind resource and turbine available power uncertainties prior to wind farm construction may contribute to significant increases in project risk and costs. Such uncertainties exist in part due to limited offshore wind measurements between 40 and 250 m and the lack of empirical methods to describe wind profiles that deviate from a priori, expected power law conditions. In this article, we introduce a novel wind profile classification algorithm that accounts for nonstandard, unexpected profiles that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Actual observations of wind shear and veer exhibit a significant variety of shapes (Pé et al, 2018), as shown in Figure 1, with four wind speed profiles from vertically profiling Doppler lidar and relevant idealized linear and logarithmic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Actual observations of wind shear and veer exhibit a significant variety of shapes (Pé et al, 2018), as shown in Figure 1, with four wind speed profiles from vertically profiling Doppler lidar and relevant idealized linear and logarithmic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The wind speed provided by Equation () is effectively a rotor‐average wind speed (also known as rotor‐equivalent or rotor‐layer wind speed), which is a better representation of the wind speed experienced by the entire rotor than the wind speed at the exact location of the hub, and ultimately provides a better estimate of the power production of the turbine 31,32 …”
Section: Methodsmentioning
confidence: 99%
“…It is well known that winds flowing at a velocity v, sweep through the blade A and increase with the cube of its velocity. The power density is expressed as using the following equation [40].…”
Section: The System Of Wind Power Potential To Produce Hydrogenmentioning
confidence: 99%